Cooperative Hydrogen Atom Transfer: From Theory to Applications - Kattamuri, Padmanabha V.; West, Julian G. (Synlett, 2021)
Hydrogen atom transfer (HAT) is one of the fundamental transformations of organic chemistry, allowing the interconversion of open- and closed-shell species through the concerted movement of a proton and an electron. Although the value of this transformation is well appreciated in isolation, with it being used for homolytic C–H activation via abstractive HAT and radical reduction via donative HAT, cooperative HAT (cHAT) reactions, in which two hydrogen atoms are removed or donated to vicinal reaction centers in succession through radical intermediates, are comparatively unknown outside of the mechanism of desaturase enzymes. This tandem reaction scheme has important ramifications in the thermochemistry of each HAT, with the bond dissociation energy (BDE) of the C–H bond adjacent to the radical center being significantly lowered relative to that of the parent alkane, allowing each HAT to be performed by different species. Herein, we discuss the thermodynamic basis of this bond strength differential in cHAT and demonstrate its use as a design principle in organic chemistry for both dehydrogenative (application 1) and hydrogenative (application 2) reactions. We hope that this overview will highlight the exciting reactivity that is possible with cHAT and inspire further developments with this mechanistic approach.1 Introduction and Theory2 Application: Dehydrogenative Transformations3 Application: Alkene Hydrogenation4 Future Applications of cHAT
Keywords: hydrogen atom transfer; cooperative hydrogen atom transfer; cooperative catalysis; radicals; bond strengths; dehydrogenation; hydrogenation